The Menisci : A Comprehensive Review of their Anatomy, Biomechanical Function and Surgical Treatment - LaPrade, Robert F.; Arendt, Elizabeth A.; Getgood, Alan; Faucett, Scott C. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book is a comprehensive journey through the pathogenesis and treatment of meniscal pathology. It details the elements that are necessary to properly understand, diagnose, and treat meniscal tears, ranging from vertical tears to radial tears and root avulsions. Treatment techniques are thoroughly described and illustrated, with presentation of the latest evidence on outcomes. The algorithmic treatment of meniscal tears has undergone a rapid transformation. We have progressed from the initial treatments involving removal of the meniscus using an open technique, to the performance of partial meniscectomies and complex meniscal repairs by means of an arthroscopic technique. The current treatment goal is to maintain the biology and mechanical integrity of this vital knee structure, an aim too often disregarded by past generations of surgeons. An explosion of new knowledge, coupled with advances in arthroscopic and surgical technology, has paved the way for wider application of approaches that help to preserve the meniscus, in the hope of preventing or delaying the development of knee arthritis. This book will have utility for all clinicians who treat meniscal lesions and will serve as a valuable resource for years to come.
Keywords: Medicine.; Orthopedics.; Rehabilitation.; Sports medicine.; elektronické knihy; electronic books